2009
DOI: 10.1002/adsc.200900251
|View full text |Cite
|
Sign up to set email alerts
|

Significant Self‐Acceleration Effects of Nitrile Additives in the Rhodium‐Catalyzed Conversion of Aldoximes to Amides: A New Mechanistic Aspect

Abstract: It was found that the catalytic activity of rhodium complexes was highly sensitive to the type of N-heterocyclic carbene (NHC) ligands in the conversion of aldoximes to amides. Among those species examined, the (cyclooctadiene)rhodium chloride-carbene complex RhACl exhibited the highest reactivity when it was employed in combination with a Brønsted acid, thus allowing mild reaction conditions. A significant rate acceleration effect resulting from the addition of nitrile additives was also observed. With the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 54 publications
(6 reference statements)
3
42
0
Order By: Relevance
“…As it is reported by several authors [6][7][8][9][10][11], benzaldoxime transforms into benzonitrile (nitrile), benzaldehyde (aldehyde) and benzamide, of which benzamide is the main (desired) product. Indeed, the transformation of benzaldoxime into benzamide is a two-step process, wherein, the selective dehydration of benzaldoxime leads to benzonitrile, which on hydrolysis converts into benzamide.…”
Section: Catalytic Activitymentioning
confidence: 74%
See 1 more Smart Citation
“…As it is reported by several authors [6][7][8][9][10][11], benzaldoxime transforms into benzonitrile (nitrile), benzaldehyde (aldehyde) and benzamide, of which benzamide is the main (desired) product. Indeed, the transformation of benzaldoxime into benzamide is a two-step process, wherein, the selective dehydration of benzaldoxime leads to benzonitrile, which on hydrolysis converts into benzamide.…”
Section: Catalytic Activitymentioning
confidence: 74%
“…Williams and his co-workers revealed the successful conversion of aldoximes into primary amides using Ru and Ir metal complexes [4,5]. It is proved that Rh complexes are good candidates for the rearrangement of aldoximes to primary amides [6][7][8]. However, Rh, Ir, and Rh containing catalytic materials are highly expensive and in addition, usage of these catalysts requires laborious workup procedure to separate the product.…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, in the rearrangement of benzaldoxime into benzamide using a supported rhodium catalyst, the reaction profile showed the initial formation of benzonitrile before subsequent formation of benzamide. [10] Additionally, the universal inertness of O-alkylated aldoximes and ketoximes towards rearrangement suggests that the transformation requires the presence of both a hydrogen and a hydroxy group.…”
mentioning
confidence: 99%
“…Chang et al have reported that nitrile additives have a self-acceleration effect on aldoxime rearrangements. [10] Within Changs study, reaction profiles were obtained for the rearrangement of benzaldoxime into benzamide, which indicated that the initial reaction rate was significantly increased in the presence of nitrile additives. Additionally, it was observed that the total concentration of nitrile remained almost constant throughout the reaction, with the amount of nitrile derived from the aldoxime increasing as the amount of nitrile additive decreased.…”
mentioning
confidence: 99%
“…Oximes and their derivatives are important intermediates in the synthesis of amides [1][2][3][4], nitro compounds, hydroximinoyl chlorides, nitrones [5], amines, azoles, nitrile oxides, chiral -sulfinyl oximes, nitriles [6][7][8], and isoxazolines [9].…”
Section: Introductionmentioning
confidence: 99%